Time-Dependent Behavior of Shrinkage Strain for Early Age Concrete Affected by Temperature Variation - Yu Qin; Zhijian Yi; Weina Wang; Di Wang (Advances in Materials Science and Engineering)
Shrinkage has been proven to be an important property of early age concrete. The shrinkage strain leads to inherent engineering problems, such as cracking and loss of prestress. Atmospheric temperature is an important factor in shrinkage strain. However, current research does not provide much attention to the effect of atmospheric temperature on shrinkage of early age concrete. In this paper, a laboratory study was undertaken to present the time-dependent shrinkage of early age concrete under temperature variation. A newly developed Material Deformation Tester (MDT), which can simulate consecutive variation of atmospheric temperature, was used to collect the shrinkage strain of specimens and temperature data. A numerical model was established to describe the thermoelastic strain of a specimen. The results show that (1) there are several sharp shrinkages up to 600 μ for early age concrete in the first 3 days; (2) the absolute value of shrinkage strain is larger than thermal strain; and (3) the difference of shrinkage strain under temperature variation or constant temperature is up to 500 μ.